Theory and Practice of Ethnicizing of Children by Means of Scientific Heritage of M.Markiewicz - Antypets, Oleksandr (Pedagogical Discourse, 2012)
The article explores the theory and practice of children’s ethnicizing, means of ethnicizing, the practice of training the national consciousness of children by means of scientific heritage of M.Markiewicz is shown: history, language, folklore, festivals, rituals, customs, folk calendar.